English

If a+1a = p and a ≠ 0; then show that: a3+1a3=p(p2-3) - Mathematics

Advertisements
Advertisements

Question

If `a + 1/a` = p and a ≠ 0; then show that:

`a^3 + 1/a^3 = p(p^2 - 3)` 

Sum

Solution

Given that `a + 1/a` = p            ...(1)

`(a + 1/a )^3 = a^3 + 1/a^3 + 3( a + 1/a )`

⇒ `a^3 + 1/a^3 = ( a + 1/a )^3 - 3( a + 1/a )`

⇒ `a^3 + 1/a^3 = (p)^3 - 3(p)`           ...[From(1)]

⇒ `a^3 + 1/a^3 = p(p^2 - 3)`

shaalaa.com
  Is there an error in this question or solution?
Chapter 4: Expansions (Including Substitution) - Exercise 4 (B) [Page 60]

APPEARS IN

Selina Concise Mathematics [English] Class 9 ICSE
Chapter 4 Expansions (Including Substitution)
Exercise 4 (B) | Q 4 | Page 60
Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×